1994
DOI: 10.2737/psw-gtr-153
|View full text |Cite
|
Sign up to set email alerts
|

California's hardwood resource: status of the industry and an ecosystem management perspective

Abstract: In an earlier publication on California's forest-zone hardwoods, 22 reasons were offered for the failure of a sustained hardwood industry to develop. This report presents knowledge developed over the past 18 years on each of these reasons. Progress is reflected in society's shift from a negative to a positive attitude towards the hardwood industry, better estimates of the inventory base and resource values, the advent of small portable sawmills, better lumber drying schedules and equipment, and recognizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…By developing this industry, demand for products from the hardwood forest would be created, which would lead to active management of the resource. McDonald and Huber (1994) also recognized that wood products were just one of four major "yields" from the land and that wildlife, water, and pleasing scenery were currently more valuable than wood products. This led to an ecosystem management perspective that was followed a year later by a philosophy and guidelines for managing for these four yields in the general forest zone, as well as in an agroforestry and urban interface setting (McDonald and Huber 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By developing this industry, demand for products from the hardwood forest would be created, which would lead to active management of the resource. McDonald and Huber (1994) also recognized that wood products were just one of four major "yields" from the land and that wildlife, water, and pleasing scenery were currently more valuable than wood products. This led to an ecosystem management perspective that was followed a year later by a philosophy and guidelines for managing for these four yields in the general forest zone, as well as in an agroforestry and urban interface setting (McDonald and Huber 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the first publication, Huber and McDonald (1992) began by detailing the history of use for three species of economically important hardwoods, especially for wood and wood products, and presented 22 reasons why the industry had not been sustained. In a second publication, they followed the progress of the industry and cautiously suggested that a viable wood processing industry was possible in the near future (McDonald and Huber 1994). By developing this industry, demand for products from the hardwood forest would be created, which would lead to active management of the resource.…”
Section: Introductionmentioning
confidence: 99%
“…Of special note in the publications by Huber and McDonald (1992) and McDonald and Huber (1994) was the acknowledgment of some realities--the most striking of which was that California hardwoods and hardwood ecosystems never really had a management philosophy, let alone some guidelines. It was not that no ideas or management possibilities had been put forth.…”
mentioning
confidence: 99%
“…Huber and McDonald (1992) presented 22 reasons for failure of a sustained hardwood industry to develop. McDonald and Huber (1994) addressed each of these and noted progress on many of them over the past 18 years. Based on this progress, it is likely that a viable hardwood industry will develop in California and Oregon in the near future.…”
mentioning
confidence: 99%
See 1 more Smart Citation